Pengaruh Budaya Organisasi, Motivasi dan Disiplin terhadap Kinerja Kasir Retail PT XYZ - Rizal Mutakin; Bobby Wiryawan Saputra (Jurnal Syntax Admiration, 2024)
The retail industry in Indonesia has experienced a post-pandemic recovery, but still faces various challenges such as economic fluctuations, changes in consumer behavior, and fierce competition. This study aims to analyze the influence of organizational culture, motivation, and discipline on cashier performance at Retail PT XYZ, one of the largest retail companies in Indonesia. This study uses a survey method with a questionnaire distributed to 100 respondents, namely cashiers who work at several PT XYZ Retail outlets in the city of Bandung. The collected data was analyzed using multiple linear regression with the help of SPSS software. The results showed that organizational culture and motivation had a positive and significant influence on cashier performance, while discipline did not have a significant influence. Simultaneously, these three variables make a significant contribution to cashier performance. An organizational culture that supports collaboration, innovation, and customer orientation, as well as motivation through rewards and career paths, is a key factor in improving performance. In contrast, work discipline that is more focused on compliance with rules is considered less effective without being supported by intrinsic motivation. This finding has implications for PT XYZ Retail management to focus more on developing organizational culture and motivation systems through continuous training, incentives, and evaluation. This finding-based policy is expected to improve operational efficiency, customer satisfaction, and the company's competitiveness in the ever-growing retail sector.